Laurence Sterne. A Sentimental Journey through France and Italy and Continuation ofthe Bramine’s Journal. The Text and Notes. The Florida Edition of the Works of Laurence Sterne. Vol. 6. Ed. Melvyn New and W. G. Day. Gainesville: UP of Florida, 2002. Ixxi - Hartvig, Gabriella (FOCUS: Papers in English Literary and Cultural Studies, 2024)
A Sentimental Journey through France and Italy and Continuation of the Bramin’s Journal is the sixth volume of the scholarly edition of the complete works of Laurence Sterne, a grandiose project by the best of the most distinguished Sterne scholars. The Florida Edition began with the publication of the text of The Life and Opinions of Tristram Shandy, Gentleman in two volumes in 1978 and was followed by references to the text, The Notes, in 1984. The following two volumes, published in 1996, contained The Sermons and Notes to the Sermons. The two texts in this bulky sixth volume, as in the earlier volumes, are presented as clean texts with the annotations and textual emendations gathered at the end ofthe volume. As with most scholarly editions, the notes and appendices fill more than half of the volume. The editors justified their decision of remaining faithful to editorial decorum on the grounds that Sterne should not be shown to readers “as a trickle oftext above a sea of commentary” while wishing at the same time that it is still not “really too sanguine to hope that Sterne will still attract lay readers in the twenty-first century” (Ixviii). The reason for the dual presentation, as New and Day claim, was that “the two works were intertwined for many months in Sterne’s own mind, and the reading ofthem should be similarly intertwined in our own” (xlvi). The Journey and the Journal equally reflect Sterne’s relationships with women, his concerns about illness and his own salvation in the final year of his life.